Multilayered autoscaling performance evaluation: Can virtual machines and containers co-scale? - Podolskiy, Vladimir; Jindal, Anshul; Gerndt, Michael (Zielona Góra: Uniwersytet Zielonogórski)
The wide adoption of cloud computing by businesses is due to several reasons, among which the elasticity of the cloud virtual infrastructure is the definite leader. Container technology allows increasing the flexibility of an application by adding another layer of virtualization. The containers can be dynamically created and terminated, and also moved from one host to another. A company can achieve a significant cost reduction and increase the manageability of its applications by allowing the running of containerized microservice applications in the cloud.
Keywords: cooperative scaling; multilayered autoscaling; autoscaling performance; autoscaling evaluation; ScaleX